”Sociobiome”: How do socioeconomic factors influence gut microbiota and enhance pathology susceptibility? - A mini-review - Nobre, José Guilherme; Alpuim Costa, D. (Frontiers in Gastroenterology, 2022)
Gut microbiota is becoming well-recognized as a key determinant of health and disease. Therefore, many studies have focused on causality and the predictive/prognostic value of the microbiota in a wide range of diseases. However, it is of greater importance to understand what sparkles microbiota changes and how these alterations contribute to an increased susceptibility to disease. A few studies have already demonstrated that gut microbiota could be modified by lifestyles, consequently leading to pathology. What if socioeconomic factors can also impact gut microbiota composition and, thus, increase the susceptibility to disease? Perhaps, this is one of the reasons that may contribute to increased inequalities between people with higher and lower socioeconomic status, in terms of health. In this review, we aim to comprehend more about this thematic and what its real impact is. Furthermore, it is important to observe how lower and higher socioeconomic factors influence microbiota composition and whether this composition can be assembled into a “sociobiome”, that can be individualized regarding a set of social and economic features. At last, we propose measures to mitigate these factors impact on gut microbiota composition.